Enhancing Learning Outcomes and Motivation in Vocational High School Students through Canvasites Learning Media Development - Hanifah Agustin; Herman Saputro; Abdul Haris Setiawan (STAI Hubbulwathan Duri, 2025)
Effective learning media can enhance students’ motivation and academic outcomes. This study aims to develop and evaluate interactive learning media based on Canvasites, assessing its effectiveness in improving student motivation and learning performance. A mixed-method approach combining Research and Development (RD) with experimental research was used. The ADDIE model guided media development through five stages: analysis, design, development, implementation, and evaluation. Data were collected through questionnaires, pretest-posttest assessments, and interviews. Descriptive analysis, feasibility criteria scoring, and statistical tests (Independent Samples Test and N-Gain) were used to evaluate effectiveness. Findings indicate that Canvasites-based interactive learning media is a viable solution for addressing learning challenges. The effectiveness test showed a significant improvement in student motivation, with experimental group participants expressing greater enthusiasm and engagement. Statistical results confirmed a significant difference (Sig. 0.05) in learning outcomes between pre- and post-intervention, with the experimental group outperforming the control group. The hypothesis test rejected Ho, confirming that the experimental group achieved higher mean scores. Additionally, N-Gain analysis classified the experimental group’s learning improvement as